2016
DOI: 10.1038/ncomms10660
|View full text |Cite
|
Sign up to set email alerts
|

A short G1 phase imposes constitutive replication stress and fork remodelling in mouse embryonic stem cells

Abstract: Embryonic stem cells (ESCs) represent a transient biological state, where pluripotency is coupled with fast proliferation. ESCs display a constitutively active DNA damage response (DDR), but its molecular determinants have remained elusive. Here we show in cultured ESCs and mouse embryos that H2AX phosphorylation is dependent on Ataxia telangiectasia and Rad3 related (ATR) and is associated with chromatin loading of the ssDNA-binding proteins RPA and RAD51. Single-molecule analysis of replication intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
161
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(172 citation statements)
references
References 53 publications
11
161
0
Order By: Relevance
“…Using time-lapse imaging, we analyzed the whole cell cycle of 46 single haploid and diploid ESCs, respectively (Figures 1G, 1H, S1B, and S1C; Movies S1 and S2). Interestingly, while the cell-cycle lengths of our diploid ESCs were consistent with previous reports (Figures 1I and S1D; Ahuja et al., 2016, Coronado et al., 2013, Re et al., 2014, Roccio et al., 2013), haploid ESCs exhibited a significantly prolonged cell cycle (Figures 1H, 1I, S1C, and S1D). Statistical analysis showed that the duration of the G1 phase was almost the same in both haploid and diploid ESCs, but the total length of the S and G2/M phases was about 5 hr longer in haploid ESCs than in diploid cells (Figures 1I, 1J, S1D, and S1E), consistent with a marginal although not statistically significant increase of the S-G2/M proportion in haploid cells (Figures 1J and S1E).…”
Section: Resultssupporting
confidence: 93%
“…Using time-lapse imaging, we analyzed the whole cell cycle of 46 single haploid and diploid ESCs, respectively (Figures 1G, 1H, S1B, and S1C; Movies S1 and S2). Interestingly, while the cell-cycle lengths of our diploid ESCs were consistent with previous reports (Figures 1I and S1D; Ahuja et al., 2016, Coronado et al., 2013, Re et al., 2014, Roccio et al., 2013), haploid ESCs exhibited a significantly prolonged cell cycle (Figures 1H, 1I, S1C, and S1D). Statistical analysis showed that the duration of the G1 phase was almost the same in both haploid and diploid ESCs, but the total length of the S and G2/M phases was about 5 hr longer in haploid ESCs than in diploid cells (Figures 1I, 1J, S1D, and S1E), consistent with a marginal although not statistically significant increase of the S-G2/M proportion in haploid cells (Figures 1J and S1E).…”
Section: Resultssupporting
confidence: 93%
“…We did not detect changes in the levels of ss C-rich linear telomeric DNA following replication stress, demonstrating that resolution of replication intermediates specifically enriches for C-rich telomeric DNA in circular conformation. We suggest that hESCs accumulate higher levels of replication stress compared to differentiated cells, which is consistent with the demonstration that replication intermediates are frequently observed in ESC, but lost after differentiation 57 .…”
Section: Discussionsupporting
confidence: 91%
“…Because origin licensing occurs in G1, daughters have more opportunity to license origins throughout the genome compared with mother cells, which have a remarkably short G1. In embryonic stem cells, which also exhibit rapid cycling with short G1, reduced licensing of replication origins creates constitutive replication stress (27). A shift in origin firing toward repetitive sequences likely also occurs during cellular aging in humans, where origins are determined by chromatin accessibility (28,29), and heterochromatic repetitive sequences open up with age (3, 4).…”
Section: Discussionmentioning
confidence: 99%